Balinese Taboo Words Used in Kerobokan Village, Badung Regency - Yogiantari, Ni Putu Egik; Budasi, I Gede; Dewi, Kadek Sintya (Universitas Muhammadiyah Kalimantan Timur, 2024)
The objective of study is to identify the taboo words used in Kerobokan Village, especially in the concept of Tri Hita Karana. This study was designed in descriptive qualitative research, which combines the sociolinguistic and ecolinguistic approaches of this research methodology. The data was obtained by utilizing in-depth interview techniques by three selected informants. Techniques of data analysis used Miles and Huberman’s theory. The findings revealed that 45 taboo words were found in Kerobokan Village, Badung Regency, which were categorized into three classifications: Parahyangan (four taboo words), Pawongan (36 taboo words), and Palemahan (five taboo words).